Two South Africans in the Portuguese Wars of Decolonization (1961-1975): it could have been better, it could have been worse - Reis, Bruno Cardoso (2016)
The two books reviewed in this article offer testimonies by two South Africans with direct experience of the Portuguese Wars of Decolonization. Al Venter is the only foreign war correspondent with direct experience in the field in all three theaters of operations of the Portuguese late colonial wars. Brigadier General van der Waals was the Vice-Consul and de facto military attaché in Luanda from 1970 to 1974. Both books show that South Africa was the foreign power most directly involved in these conflicts and with most vital interests at stake. It has, consequently, every reason to pay the closest possible attention to them. Both books also show that, despite the close cooperation in the field between South Africa and Portugal, especially after 1968, the mainstream South African view of these counter-insurgencies was often very critical of the Portuguese war effort.